The utilization of education among university educated employees in private companies and public institutions - Eðvarðsson, Ingi Rúnar; Óskarsson, Guðmundur Kristján; Bergsteinsson, Jason Már (Stjórnsýslustofnun, 2017)
The aim of the article is to examine whether there is a difference in the utilization of education among university educated employees in private companies on the one hand and public institutions on the other. The target population of the research was based on a random sample drawn from the National Population Register by the National Survey of the Social Science Research Institute of the University of Iceland from 9 March to 9 April 2016. The survey included 2,001 individuals, aged 18 or above, from all over the country. A total of 1,210 persons responded to the survey. This research only involved those participants in the sample who had completed a university education and were salaried employees in Iceland. After data cleansing, 374 participants remained, 178 males and 196 females. The initial results of the research indicated that 20.3% of participants were over-educated for their jobs. The majority of females work in public companies, while the majority of males work in private companies. Individuals with under-education are most likely to be found within public companies, at the same time as over-educated individuals are most likely to be found in private companies (the difference lies in the under- and over-education of females). Those working in public companies come primarily from educational and health sicences, while engineers and natural sicentists work primarily at private companies. Incomes are higher in private companies. Markmið greinarinnar er að kanna hvort munur sé á hagnýtingu þekkingar meðal háskólamenntaðs fólks sem vinnur annars vegar í einkareknum fyrirtækjum og í opinberum stofnunum hins vegar. Úrtak rannsóknarinnar byggðist á tilviljunarúrtaki úr þjóðskrá sem Þjóðmálakönnun Félagsvísindastofnunar Háskóla Íslands framkvæmdi 9. mars til 9. apríl 2016. Könnunin náði til 2.001 einstaklings á aldrinum 18 ára og eldri á landinu öllu og svöruðu 1.210 þeirra könnuninni. Í þessari rannsókn var aðeins litið til þeirra þátttakenda í úrtakinu sem höfðu lokið háskólanámi og voru í launaðri vinnu á ...